2014
DOI: 10.1111/aogs.12494
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, nongenetic and epigenetic risk determinants in developmental programming of type 2 diabetes

Abstract: Low birthweight (LBW) individuals and offspring of women with gestational diabetes mellitus (GDM) exhibit increased risk of developing type 2 diabetes (T2D) and associated cardiometabolic traits in adulthood, which for both groups may be mediated by adverse events and developmental changes in fetal life. T2D is a multifactorial disease occurring as a result of complicated interplay between genetic and both prenatal and postnatal nongenetic factors, and it remains unknown to what extent the increased risk of T2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 60 publications
2
39
0
Order By: Relevance
“…15,[42][43][44] Other investigators have hypothesized that women in whom gestational diabetes develops may carry a greater genetic load of variants associated with β-cell dysfunction and insulin resistance, which, in turn, increases their babies' genetic load for these conditions. 45,46 We also observed that maternal hyperglycemia was associated with increased newborn birth weight, more adipose tissue in newborns, a higher proportion of infants who were large for gestational age and a larger placenta. Furthermore, babies of women with gestational diabetes had reduced insulin sensitivity.…”
Section: Discussionmentioning
confidence: 59%
“…15,[42][43][44] Other investigators have hypothesized that women in whom gestational diabetes develops may carry a greater genetic load of variants associated with β-cell dysfunction and insulin resistance, which, in turn, increases their babies' genetic load for these conditions. 45,46 We also observed that maternal hyperglycemia was associated with increased newborn birth weight, more adipose tissue in newborns, a higher proportion of infants who were large for gestational age and a larger placenta. Furthermore, babies of women with gestational diabetes had reduced insulin sensitivity.…”
Section: Discussionmentioning
confidence: 59%
“…Although the handgrip test is considered a valid marker for frailty [9,11], we cannot exclude that a multi-component definition of frailty could have shown more marked differences. Furthermore, we cannot exclude the influence of genetic background on fetal programming from maternal obesity, but there is solid evidence that fetal programming has a bigger role than genetic background [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…The genetic background of the offspring interacts with intrauterine programming. However, it has been argued that maternal obesity is more important than genetic factors in determining health in adult life both in humans [5,6] and animal models [7], which have low genetic variability. Furthermore, there is a greater association between maternal BMI and the manifestations of overweight in children compared with paternal BMI [8].…”
Section: Introductionmentioning
confidence: 99%
“…This disease generally develops after the age of 40, but it is now increasingly diagnosed in children and young adults [1]. There is increasing experimental and epidemiological evidence that T2D and obesity, which is an important risk factor for T2D, may originate during critical windows of prenatal and early postnatal development [2]. These findings are consistent with the developmental programming of health and disease (DOHAD) hypothesis which proposes that physiology and structure of the developing fetus may be adapted in response to adverse developmental conditions, such as poor nutrition, predisposing to various pathological conditions later in life [3].…”
Section: Introductionmentioning
confidence: 99%
“…The precise mechanisms underlying developmental programming of obesity and T2D are far from being completely elucidated. However, recent studies suggest that epigenetics (heritable changes in gene function that do not involve changes to the DNA sequence) is the most plausible mechanistic pathway for the relationship between adverse developmental conditions and health outcomes in later life [2].…”
Section: Introductionmentioning
confidence: 99%